2017
DOI: 10.1097/cco.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics-mediated suppression of cancer

Abstract: Despite laboratory-based studies having demonstrated encouraging outcomes that probiotics possess antitumor effects, the benefits should not be exaggerated before we get more results from human clinical trials. These are very important before the medical community can accept the use of probiotics as an alternative therapy for cancer control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 78 publications
1
44
0
4
Order By: Relevance
“…The study of inhibitory effects of probiotic Lactobacillus on the Growth of Human Colonic Carcinoma Cell Line HT-29 showed that Lactobacillus can inhibit the growth of colonic carcinoma cells and may lead to apoptosis. Live Lactobacillus acidophilus and Lactobacillus rhamnosus GG, Lactobacillus casei, Lactobacillus reuteri has been confirmed to induce apoptotic cell death in both murine and human colon carcinoma cell lines as well as an experimental tumor model [104][105][106][107][108].…”
Section: Prevention and Management Of Cancermentioning
confidence: 99%
“…The study of inhibitory effects of probiotic Lactobacillus on the Growth of Human Colonic Carcinoma Cell Line HT-29 showed that Lactobacillus can inhibit the growth of colonic carcinoma cells and may lead to apoptosis. Live Lactobacillus acidophilus and Lactobacillus rhamnosus GG, Lactobacillus casei, Lactobacillus reuteri has been confirmed to induce apoptotic cell death in both murine and human colon carcinoma cell lines as well as an experimental tumor model [104][105][106][107][108].…”
Section: Prevention and Management Of Cancermentioning
confidence: 99%
“…Disorders ranging from inflammatory diseases to several types of cancer, including colon cancer, are believed to benefit from probiotics (72,73). In fact, a combination of microorganisms seems to act much more efficient than a single microorganism.…”
Section: Microbiota Contribution In Favor Of Tumor Protectionmentioning
confidence: 99%
“…Contribution of microbiota as a health-promoting factor is best exemplified by the administration of probiotics, a group of live microorganisms which are shown to be beneficial for the host (72). Disorders ranging from inflammatory diseases to several types of cancer, including colon cancer, are believed to benefit from probiotics (72,73).…”
Section: Microbiota Contribution In Favor Of Tumor Protectionmentioning
confidence: 99%
See 2 more Smart Citations